Reviews of Books (International review of mission, 1952)
Books Reviewed in this article: THE THEOLOGY OF MISSIONS: Beiträge zur Missionswissenschaft und Evangelischen Religionskunde. THE THEOLOGY OF MISSIONS: 1. Das Taufproblem in der Mission. By Hans-Werner Gensichen. DM. 5. 1951. THE THEOLOGY OF MISSIONS: 2. Weltmission und Weltende. By Gerhard Rosenkranz. THE AMERICAN Y.M.C.A. CENTURY: History of the Y.M.C.A. in North America. By C. Howard Hopkins. THE HISTORY OF THE S.P.G.: Into all Lands. The History of the Society for the Propagation of the Gospel in Foreign Parts, 1701–1950. By H. P. Thompson. INDIA'S CHALLENGE TO THE CHRISTIAN CONSCIENCE: The Christian Task in Independent India. By A. J. Appasamy. A JEWISH REJECTION OF HISTORY: A Partisan History of Judaism. By Elmer Berger. HANS EGEDE: Hans Egede. Colonizer and Missionary of Greenland. By Louis Bobé. THE VENTURE OF FAITH: A Retrospect. By J. Hudson Taylor. THE VENTURE OF FAITH: Das Wagnis des Glaubens: Leben und Wirken James Hudson Taylor's. By Anna Oehler. MENDE LIFE AND CULTURE: The Mende of Sierra Leone: A West African People in Transition. By K. L. Little. AGE-GROUP VILLAGES IN SOUTHERN TANGANYIKA: Good Company. A Study of Nyakyusa Age- Villages. By Monica Wilson. THE BASUTO—PAST AGAINST FUTURE: The Basuto. By Hugh Ashton. GUIDES TO THE STUDY OF CHURCH UNITY: The Church in the Purpose of God. By Oliver S. Tomkins. GUIDES TO THE STUDY OF CHURCH UNITY: Exploring Paths of Church Unity. By James W. Kennedy. GUIDES TO THE STUDY OF CHURCH UNITY: The Church's Unity. By J. D. McCaughey and R. P. C. Hanson. A SOUTH INDIA DIARY: That All May Be One. By J. E. Lesslie Newbigin: New York: Haddam House, Association Press. USD1.50. 1952. (American edition of A South India Diary. THE HOLY LAND IN PICTURES: The Catholic Shrines of the Holy Land. By the Very Reverend Paschal Kinsel and the Reverend Leonard Henry. With photographs by Alfred Wagg.